2017
DOI: 10.1093/ntr/ntx231
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Early Onset of E-cigarette Use and Cigarette Smoking and Other Substance Use Among US Adolescents: A National Study

Abstract: To date, no studies have examined the probability of cigarette smoking and other substance use behaviors as a function of age at onset of e-cigarette use. In the present study, early onset of e-cigarette use was significantly associated with increased odds of cigarette smoking and other substance use behaviors. The findings reinforce the importance of addressing a wide range of substances including alcohol, traditional cigarettes, and marijuana when developing early primary prevention efforts to reduce e-cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 45 publications
(94 reference statements)
3
48
1
1
Order By: Relevance
“…Due to the lack of studies on the dual use of illicit drugs and e-cigarettes in Canada, it is not possible to compare these results to previous Canadian data to assess trends. However, some international studies have shown findings similar to those in the present study [15][16][17]34]. Additionally, even fewer studies have explored the potential use of ecigarettes as illicit drug delivery systems.…”
Section: Discussionsupporting
confidence: 81%
“…Due to the lack of studies on the dual use of illicit drugs and e-cigarettes in Canada, it is not possible to compare these results to previous Canadian data to assess trends. However, some international studies have shown findings similar to those in the present study [15][16][17]34]. Additionally, even fewer studies have explored the potential use of ecigarettes as illicit drug delivery systems.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies show that adolescents who engage in e-cigarette use only are at greater risk for other types of substance use, however, these studies have not fully considered the role of early onset vs late onset of e-cigarettes relative to dual users across multiple age groups. 10,11,22,23,28 The results from this study extend prior work and suggest that earlier initiation of e-cigarette use remains a substantial risk factor for other types of substance use-even for this lower risk group of e-cigarette only users. Taken together, these findings indicate that adolescents who engage in early onset of e-cigarette use (ecigarette use only or dual use) should be assessed for substance-related problems based on their increased risk for polysubstance use.…”
Section: Discussionsupporting
confidence: 78%
“…JUUL’s high nicotine concentration raises concern that it is serving as a gateway to nicotine addiction among a sizeable number of adolescents. Studies show that nicotine-addicted teen vapers often adopt use of more dangerous combustible tobacco types 52–56. The rising use of vapour devices in schools may portend use of other substances.…”
Section: Discussionmentioning
confidence: 99%